(3TQM aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3gh Cfg GLJfH Yf GdMQGe djS MceG TQYjG Hd gh Mce jfJRYg GdYbd ef GdCOdI GdeJYdbI HGdYfGhjf GdhGbYjI HeYfi Cf GdYbd HYO edGMXJg dG LJfH Yf GdNeQ jfRY efg MceG hgh hLhH GdGLJfGHs
(3BNQgG (B:s
(3BNQgG(B: (3GdCeQ GdQGHY Cf dG jchf GdeQGO HGdMJjGW gh GdGMJjGW aj GdaJhi aEfg dG cdGe dfG ajg hdcf gPg GdCehQ ZjQ eSdeIs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs